2014
DOI: 10.1097/igc.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Patient-Reported Outcomes in Endometrial Cancer Clinical Trials

Abstract: Although there have been some studies addressing QoL and PROs in EC, we have identified deficiencies and gaps in our knowledge. Careful consideration of QoL and PROs end points and how to include them in clinical trials will result in a better appreciation of how treatments can impact on patients QoL and lead to conduct interventions to reduce late effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
1
26
0
2
Order By: Relevance
“…Characteristics associated with HRQoL have mostly been evaluated in cross-sectional studies [6][7][8][9] which included small and selective samples [6] or did not cover a broad range of HRQoL outcomes [10]. Other studies evaluated HRQoL as part of a clinical trial, with selective samples [8,11]. As evaluated in clinical trials, a poorer HRQoL has been found in patients with a higher tumor stage [12] and in patients receiving radiotherapy or chemotherapy compared to patients without adjuvant therapy [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics associated with HRQoL have mostly been evaluated in cross-sectional studies [6][7][8][9] which included small and selective samples [6] or did not cover a broad range of HRQoL outcomes [10]. Other studies evaluated HRQoL as part of a clinical trial, with selective samples [8,11]. As evaluated in clinical trials, a poorer HRQoL has been found in patients with a higher tumor stage [12] and in patients receiving radiotherapy or chemotherapy compared to patients without adjuvant therapy [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high mortality of cancer, patients diagnosed with cancer survive much longer than ever before due to early detection [1–3], effective treatment [4, 5] and improved health management [6]. However, compared with the general population, most cancer survivors experience poorer quality of life (QOL) in both physical and psychological aspects after cancer diagnosis and its treatment [7, 8]. Meanwhile, longer survival time makes QOL an even more important outcome measure for the population with metastatic disease, for whom a cure is probably not the goal.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life (QOL) is an increasingly important issue in oncology. Careful consideration of QOL and patient-reported outcomes (PROs) and the integration of these end points in clinical trials is critical to the understanding of how various treatments impact QOL, catalysing the development of effective interventions to reduce late effects (Joly et al, 2014). This is especially important in patients with EC, who generally have promising oncologic outcomes, and long overall survivals.…”
Section: Introductionmentioning
confidence: 99%